Delivery risks and outcomes associated with grand multiparity. (12th December 2022) - Lee, Kate E.; Wen, Timothy; Faye, Adam S.; Huang, Yongmei; Hur, Chin; Friedman, Alexander M.
Abstract: Background: There is limited recent US national data on risk for adverse outcomes associated with grand multiparity. Objective: To examine the association between grand multiparity and severe maternal morbidity (SMM) and other adverse outcomes during delivery hospitalizations in the United States. Methods: This repeat cross-sectional study evaluated delivery hospitalizations from 2000 through the third quarter of 2015 to women aged 15–54 in the National (Nationwide) Inpatient Sample database. Temporal trends in deliveries to women with grand multiparity were analyzed using the Cochran–Armitage trend test. The primary outcome studied was SMM, a composite of adverse outcomes defined by the Centers for Disease Control and Prevention. The exposure of interest was grand multiparity diagnosis during delivery hospitalization. Other adverse outcomes analyzed included placental abruption, preterm delivery, postpartum hemorrhage, disseminated intravascular coagulation, shock, hysterectomy, pulmonary edema and acute heart failure, transfusion of blood or blood products, hypertensive diseases of pregnancy, cesarean delivery, eclampsia, and acute renal failure. Log linear regression models were performed to determine the relationship between grand multiparity and adverse outcomes with measures of association demonstrated as unadjusted (RR) and adjusted risk ratios (aRR) with 95%CIs. Results: From 2000 to 2015, there were an estimated 62, 672, 862 hospital deliveries with 386, 019 deliveries in the setting of grand multiparity. The number of deliveries with a grand multiparity diagnosis increased over the study period from 4.2 per 1000 deliveries in 2000 to 8.6 per 1000 in 2015 ( p < .01). Women with grand multiparity were more likely to be older, have comorbidities, be Hispanic or non-Hispanic Black, be from a lower ZIP code income quartile, have Medicaid insurance, and present to an urban teaching hospital for delivery ( p < .01 for all). On univariable analysis, grand multiparity was associated with SMM (RR 1.27, 95%CI 1.23–1.32). However, in adjusted analyses accounting for hospital, clinical, and demographic factors, women with grand multiparity were at lower risk of SMM (aRR 0.93, 95%CI 0.89, 0.96). On analysis of individual adverse outcomes, grand multiparity was associated with a higher risk of placental abruption (RR 1.28, 95%CI 1.24–1.31), preterm delivery (RR 1.17, 95%CI 1.16–1.18), postpartum hemorrhage (RR 1.30, 95%CI 1.28–1.32), disseminated intravascular coagulation (RR 1.23, 95%CI 1.16–1.31), shock (RR 2.50, 95%CI 2.20–2.85), hysterectomy (RR 3.20, 95%CI 3.30, 3.41), pulmonary edema and acute heart failure (RR 1.33, 95%CI 1.24–1.42), and transfusion of blood or blood products (RR 1.74, 95%CI 1.70–1.79). Conversely, grand multiparity was associated with a lower risk of hypertensive diseases of pregnancy (RR 0.85, 95%CI 0.84–0.86), cesarean delivery (RR 0.96, 95%CI 0.95–0.96), and eclampsia (RR 0.69, 95%CI 0.60–0.79). There was no significant association between grand multiparity and acute renal failure. Conclusions: Delivery hospitalizations with a grand multiparity diagnosis were not associated with increased risk for SMM in adjusted analysis. Grand multiparity was associated with increased risk for hysterectomy and shock although absolute increased risk for these complications was small.